Thermodynamic Study of Metal Corrosion and Inhibitor Adsorption of Hexamine in Mild Steel - Bozorg, M.; Shahrabi, T.; Neshati, J.; Chaghervand, Hamed (Asian Journal of Chemistry, 2011)
In this study, the hexamine adsorption and thermodynamic parameters on steel in 1M HCl solution was studied. Electrochemical impedance and polarization technique at different hexamine concentrations were done and good inhibition in presence of 700 ppm hexamine was obtained in stagnant and 25 ºC. In this hexamine concentration, the calcualted value of activation energy is found to be 85.2 KJ/mol. Free energy and enthalpy of the adsorption were calculated -31 and -13 KJ/mol, respectively according to Langmuir isotherms and physical adsorption. Entropy of the adsorption was calculated by thermodynamic fundamental equation as well. Moreover, kinetic adsorption of hexamine studied by impedance spectroscopy. Result showed the inhibition efficiency increased up to 90 % after 12 h. The effect of hydrodynamic conditions was studied by variation in rotating speed. The results indicated that higher rotating speed negatively affected the inhibition properties.